Mutation distributions and clinical correlations of PIK3CA gene mutations in breast cancer - AKKİPRİK, MUSTAFA; ÖZER, SIDIKA AYŞE (SAGE PUBLICATIONS LTD, 2016)
Breast cancer (BCa) is the most common cancer and the second cause of death among women. Phosphoinositide 3-kinase (PI3K) signaling pathway has a crucial role in the cellular processes such as cell survival, growth, division, and motility. Moreover, oncogenic mutations in the PI3K pathway generally involve the activation phosphatidylinositol-4,5-bisphosphate 3-kinase-catalytic subunit alpha (PIK3CA) mutation which has been identified in numerous BCa subtypes. In this review, correlations between PIK3CA mutations and their clinicopathological parameters on BCa will be described. It is reported that PIK3CA mutations which have been localized mostly on exon 9 and 20 hot spots are detected 25-40 % in BCa. This relatively high frequency can offer an advantage for choosing the best treatment options for BCa. PIK3CA mutations may be used as biomarkers and have been major focus of drug development in cancer with the first clinical trials of PI3K pathway inhibitors currently in progress. Screening of PIK3CA gene mutations might be useful genetic tests for targeted therapeutics or diagnosis. Increasing data about PIK3CA mutations and its clinical correlations with BCa will help to introduce new clinical applications in the near future.
Keywords: Breast cancer; PIK3CA; Mutation; p110 alpha; PI3K; CIRCULATING TUMOR-CELLS; EXON 20 MUTATIONS; PI3K PATHWAY; PTEN LOSS; NEOADJUVANT CHEMOTHERAPY; ONCOGENIC MUTATIONS; HOTSPOT MUTATIONS; COLORECTAL-CANCER; KINASE-ACTIVITY; TRASTUZUMAB